Pengaruh Earning Per Share Terhadap Harga Saham Pada Perusahaan Tambang Batubara Yang Terdaftar Di Bursa Efek Indonesia (2020-2022) - Mintauli Debataraja (IJAcc, 2023)
This study aims to determine the effect of Earning Per Share on Share Prices in coal mining companies listed on the IDX in the 2020-2022 period. The method used in this research is a quantitative method. The population in this study are companies in the coal mining sector on the Indonesia Stock Exchange for the 2020-2022 period, totaling 19 issuers. The sample used is the purposive sampling method with the following criteria: (1) New stone mining sector companies registered on the IDX in 2020-2022, (2) issuing financial reports. The results of the study show that Earning Per Share (EPS) has a positive effect on stock prices in changes to coal mines listed on the IDX in 2020-2022. The remaining 87% is influenced by other factors such as the economic level of the community, the inflation rate and the rupiah exchange rate against the dollar.